ANALYSIS OF THE USE OF VARIATION OF MEDIA IN INQUIRY LEARNING AND LEARNING STYLES ON PHYSICS LEARNING OUTCOMES IN CLASS X HIGH SCHOOL - MOH. EDI SUYANTO (BIOEDUKASI, 2021)
Technology and media have always been an integral part of many strategies. Comparative studies over the years have shown that it is learning strategies that facilitate learning, not technology and media. The purpose of this study was to analyze the interaction of the use of various media in inquiry learning and learning styles on physics learning outcomes. This study used a quasi-experimental design with a factorial design (3x3) which involved three groups of subjects, taking into account the existence of a moderator variable which was thought to influence the experiment on the results obtained. Research data were collected using: (1) a visual-auditorial-kinesthetic learning style questionnaire; (2) pre-test and post-test learning outcomes. The three research hypotheses were tested using a two-way analysis of variance (ANAVA) technique. All statistical analyzes used the SPSS statistical program and all null hypothesis testing was performed at the 5% significance level. The results showed that there was an interaction between the use of various media in inquiry learning and learning styles towards the physics learning outcomes of class X high school students